Effect of Avocado (Persea americana M.) Juice on Superoxide-Dismutase (SoD) and Interleukin-6 (IL-6) Levels - Shinta, Sopia; Wibowo, Joko Wahyu; Zulaikhah, Siti Thomas (Lighthouse Publishing, 2023)
Cigarette smoke contains oxidants or free radicals, about 4700 harmful chemicals. The high level of free radicals in the body triggers the emergence of Reactive Oxygen Species (ROS), which results in oxidative stress. This can occur if there is an imbalance between the number of oxidants and antioxidants. In this process, there is an O2 leak that will turn into a superoxide radical (O2-) that can form pro-inflammatory cytokines such as IL-6. The purpose is to determine the effect of avocado juice administration on Superoxide Dismutase (SOD) levels and IL-6 levels in male Wistar rats exposed to cigarette smoke. This study used Post Test Only Control Group Design. Samples were taken from 20 male rats that entered the inclusion criteria and divided into four random groups, namely K1, K2, K3, and K4. K1 is the control group with standard feed without exposure to cigarette smoke; K2 is the treatment group with standard feed given exposure to cigarette smoke, K3 was given standard feed plus avocado juice at a dose of 2.7 grams /day. Meanwhile, the K4 group was given standard feed plus avocado juice at a 5.4 grams/day dose. However, both were given 14 days of exposure to cigarette smoke. On the 15th day, male Wistar rats were drawn blood to examine the SOD using spectrophotometry and IL-6 using ELISA. Data were analysed using the One-Way Anova different test and continued with the Post hoc Tukey test. The average SOD levels were highest in the K1 with a value of 83,23, and IL- 6 levels were highest in the K2 with a value of 79,93. The One-Way ANOVA test obtained results that SOD and IL-6 levels in each group with a value of P<0.05, which means that there were significant differences in influence. Giving avocado juice has an effect on increasing levels of SOD and decreasing levels of IL-6.